A Bibliometric Analysis of Marxian Political Economy Research in Canada - Singh, Paramjit; Akhter, Mohd; Aqil, Mohammad; Ahmad, Shakil (Qualitative and Quantitative Methods in Libraries; Vol 11 No 2 (2022): June issue 2022, 2022)
The present Scopus-based study is the first to examine Marxian political economy research by Canadian social scientists. The data analysis was done using bibliometric software, including MS Excel, VOS Viewer, and biblioshiny (R Studio). The growth of publications over time and their citations are analyzed first, followed by top authors, leading institutions, international collaboration, top `journals. Further, the co-occurrence of keywords and top-cited articles are analyzed. The results show that Giroux, H A from McMaster University, is the most productive author. At the same time, Peck, J from The University of British Columbia is most influential among the top authors, and the University of Toronto is the most productive institution. The results also reveal that capitalism, neoliberalism, globalization, democracy, and ideology are the most important research topics.